Pengaruh Faktor Kepuasan Kerja terhadap Employee Engagement di Perwiratama Group - Windy Putri Arianti; Musa Hubeis; Herien Puspitawati (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2020)
Perwiratama Group is one of the companies in the business industry that must compete with another company in the same segmentation. One way to compete is by knowing the factors of job satisfaction and employee engagement at Perwiratama Group. These variables are job satisfaction factors and employee engagement. Respondents of this study were 84 employees of Perwiratama Group in four business units. The research method used is multiple linear regression. The result of this study shows that job satisfaction variable on work, job satisfaction on salary, and job satisfaction on co-workers influence employee engagement variables. While job satisfaction variables on promotion and job satisfaction on supervision of employee engagement variables have no effect. Adjusted R Square results are 0.431 or 43.1%. This value shows that the variables of job satisfaction factors (job satisfaction at work, job satisfaction on salary, job satisfaction on promotion, supervision of job satisfaction, and job satisfaction on colleagues) affect employee engagement variables at Perwiratama Group by 43.1%, while the rest is influenced by other factors not examined in this study.